PENGEMBANGAN MEDIA PEMBELAJARAN POWER POINT MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS VII SEMESTER 1 DI SEKOLAH MENENGAH PERTAMA NEGERI 20 MALANG - Dinna Lestari (LPPM STKIP PGRI Sidoarjo, 2020)
Audio visual media using the power point program is a learning resource that can be used as a learning medium in schools, especially in science subjects, the subject of grouping living things. Based on the results of observations made by developers at SMP Negeri 20 Malang, it turns out that the teacher only uses textbooks as the only learning medium. For this reason, developers make alternative problem solvers by developing power point media as a learning medium. The purpose of developing this power point media is to assist teachers in the teaching and learning process in order to achieve predetermined learning objectives. Also as a medium that can attract students' attention in learning activities so that students can be motivated. From the validation results show; 1) validation of media experts shows results of 80%, 2) validation of material experts shows results of 93.75%, 3) while in class validation shows results of 80.15% based on the above research shows that the power point which is developed has high validity.